Screening of different sample types associated with sheep and cattle for the presence of nematophagous fungi in China - Cai, Kui-Zheng; Liu, Jun-Lin; Liu, Wei; Wang, Bo-Bo; Xu, Qiang; Sun, Long-Jie; Chen, Ming-Yue; Zhao, Ming-Wang; Wu, Jia-Yan; Li, Xiao-Shan; Yang, Jing; Wei, Shuan; et al. (Journal of basic microbiology, 2016)
A total of 1502 samples, including feces of sheep (793) and cattle (348), pasture soil (118), dung compost (147) and barn soil (96), were examined between October 2012 and August 2014 to discover potential strains of nematophagous fungi for the biological control of livestock‐parasitic nematodes. These samples were collected from 87 sites located in 48 counties of 20 provinces (autonomous regions/municipalities) of China. Fungi were identified down to a species level. Four hundred and seventy‐seven isolates, which were distributed in 8 genera and 28 taxa, were identified as nematophagous fungi. Nematode‐trapping fungi included 17 species and one unidentified species of Arthrobotrys, two of Dactylella, Drechslerella dactyloides, and Duddingtonia flagrans. Five identified species and two unidentified species of endoparasitic fungi were isolated. The predominant species from all regions were Arthrobotrys oligospora, followed by Arthrobotrys musiformis, Arthrobotrys (Monacrosporium) thaumasiun, and Arthrobotrys (Monacrosporium) microscaphoides. Species with adhesive networks were the most frequently isolated. Among the endoparasitic fungi, Podocrella harposporifera (Harposporium anguillulae) was the most common species, followed by Harposporium lilliputanum and Harposporium arcuatum. Based on Shannon diversity index, the diversity levels of nematophagous fungi were relatively higher in samples associated with cattle, barn soil, and subtropical monsoon climate zone. Three species isolated from this study, namely, Duddingtonia flagrans, Arthrobotrys salina (Monacrosporium salinum), and Arthrobotrys oligospora var. sarmatica, are newly recorded in China, and 20 species (including one unidentified species) are newly recorded in sheep and cattle barn soils worldwide.